1993
DOI: 10.1007/bf01225235
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization and dynamics of paraquat in the stomach and esophagus of rats

Abstract: The dynamics of paraquat in the stomach and esophagus of rats were demonstrated using immunohistochemical techniques. The Rats were killed 3h, 12h, 24h, 3 days, 7 days and 10 days after intravenous administration of paraquat. In the stomach, paraquat was localized in the epithelial cells between 24 h and 10 days after injection, whereas in the esophagus, paraquat was localized in epithelial cells and the lamina propria mucosa between 12h and 10 days after administration. Although these findings were similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, the dynamics of PQ in rats has been rarely investigated. Studies[ 38 , 39 ] revealed that plasma paraquat concentration of rats maintained high within 24 hours after PQ poisoning and vanished within 72 hours, which can be detected in the lungs, stomach and intestine 10 days after administration of PQ.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dynamics of PQ in rats has been rarely investigated. Studies[ 38 , 39 ] revealed that plasma paraquat concentration of rats maintained high within 24 hours after PQ poisoning and vanished within 72 hours, which can be detected in the lungs, stomach and intestine 10 days after administration of PQ.…”
Section: Discussionmentioning
confidence: 99%